Farewell Luncheon at Cedar Lanes Bowling Alley for Tomar Mason II - Watkins, Howard::::::::: (1986)
On left: Sam Vallis, Val Weston, Donald Fischbach, Mary Louise Frampton and Doug Jensen; on right: Polly Getz and Darlene Azevedo